2017
DOI: 10.1038/s41593-017-0040-x
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ activity signatures of myelin sheath formation and growth in vivo

Abstract: During myelination, individual oligodendrocytes initially over-produce short myelin sheaths that are either retracted or stabilised. By live imaging oligodendrocyte Ca2+ activity in vivo, we find that high-amplitude long-duration Ca2+ transients in sheaths prefigure retractions, mediated by calpain. Following stabilisation, myelin sheaths grow along axons, and we find that higher frequency Ca2+ transient activity in sheaths precedes faster elongation. Our data implicate local Ca2+ signalling in regulating dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
181
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(192 citation statements)
references
References 26 publications
11
181
0
Order By: Relevance
“…There are a number of signals that could be modified by iTBS to increase internode length. For example, GABAergic signaling in neocortical slices, cultured from P8 mice, is associated with increased internode length (Hamilton et al, ), however, iTBS also increased internode length in the CC, suggesting that longer internodes may instead result from increased glutamate‐induced calcium signaling in the developing myelin sheaths (Baraban, Koudelka, & Lyons, ; Krasnow, Ford, Valdivia, Wilson, & Attwell, ). While iTBS could lengthen internodes by modulating neurons, the alternative is that it has a direct effect on the extending internodes of maturing oligodendrocytes, perhaps influencing local calcium signaling (Grehl et al, ), and further research is required to dissect the primary and secondary effects of iTBS on these cells.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of signals that could be modified by iTBS to increase internode length. For example, GABAergic signaling in neocortical slices, cultured from P8 mice, is associated with increased internode length (Hamilton et al, ), however, iTBS also increased internode length in the CC, suggesting that longer internodes may instead result from increased glutamate‐induced calcium signaling in the developing myelin sheaths (Baraban, Koudelka, & Lyons, ; Krasnow, Ford, Valdivia, Wilson, & Attwell, ). While iTBS could lengthen internodes by modulating neurons, the alternative is that it has a direct effect on the extending internodes of maturing oligodendrocytes, perhaps influencing local calcium signaling (Grehl et al, ), and further research is required to dissect the primary and secondary effects of iTBS on these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting such a premise, is emerging evidence that neuronal activity can indeed directly regulate the length of myelin sheaths both in vitro and in vivo in zebrafish and rodents (Fields et al, ; Hines, Ravanelli, Schwindt, Scott, & Appel, ; Koudelka et al, ). Furthermore, recent live‐imaging studies in zebrafish indicate that distinct localized codes of Ca 2+ activity in myelin sheaths prefigure sheath elongation and shrinkage, and that at least some of these myelin Ca 2+ signatures are driven by neuronal activity (Baraban, Koudelka, & Lyons, ; Krasnow, Ford, Valdivia, Wilson, & Attwell, ). Therefore, distinct forms of neural activity might fine‐tune sheath growth along axons, which may have the consequence of influencing conduction velocity.…”
Section: Myelinmentioning
confidence: 99%
“…For example, it was shown that glutamate released by axons is sensed by AMPA receptors on oligodendrocyte precursor (NG2) cells, which influences their proliferation and differentiation [17,19,32,[64][65][66]. There is also firm evidence that glutamate derived from active axons is sensed by AMPA and NMDA receptors expressed on the surrounding myelin sheath, resulting in calcium signals proposed to play a central role in coupling axonal activity and integrity with oligodendrocyte metabolism and driving formation of myelin [67][68][69][70][71][72]. Metabolic support of axons was moreover suggested to be provided by astrocytes, which break down glycogen and release lactate into the extracellular space that can then be taken up by axons during periods of high energy demand [73,74].…”
Section: Relevance Of Different Sodium Influx Pathwaysmentioning
confidence: 99%